Using RSSI-Based Bluetooth Low Energy for Indoor Location Detection - Sumer, Niyazi Nadi; Atakli, Nevzat; Kucur, Oğuz (IEEE, 2020)
People often spend time in buildings such as offices, hospitals, factory workspaces, and other interiors. Today, positioning and navigation are of great importance in such environments. Global Positioning System (GPS), which is commonly used for location information, cannot be used indoors. Therefore, we need the new technology of the real-time location system. In this research, the use of Bluetooth Low Energy (BLE) RSSI was investigated. The mathematical filters median, mod, max, mean were tried to ensure the accuracy of RSSI. A different triangulation algorithm was used to calculate the positioning. In the study, all calculations and algorithms have been tried in real environments and the results have been recorded. With this work, better algorithms for indoor positioning with BLE technology have been developed and the position accuracy has been improved.
5th International Conference on Computer Science and Engineering (UBMK) -- SEP 09-11, 2020 -- Diyarbakir, TURKEY
Keywords: IoT; triangulation; localization; RSSI; Bluetooth Low Energy